Creating a human head finite element model using a multi-block approach for predicting skull response and brain pressure. Issue 2 (25th January 2019) - Cai, Zhihua; Xia, Yun; Bao, Zheng; Mao, Haojie
Abstract: To better understand head injuries, human head finite element (FE) models have been reported in the literature. In scenarios where the head is directly impacted and measurements of head accelerations are not available, a high-quality skull model, as well as a high-quality brain model, is needed to predict the effect of impact on the brain through the skull. Furthermore, predicting cranial bone fractures requires comprehensively validated skull models. Lastly, high-quality meshes for both the skull and brain are needed for accurate strain/stress predictions across the entire head. Hence, we adopted a multi-block approach to develop hexahedral meshes for the brain, skull, and scalp simultaneously, a first approach in its kind. We then validated our model against experimental data of brain pressures (Nahum et al., 1977 ) and comprehensive skull responses (Yoganandan et al., 1995, Yoganandan et al., 2004, and Raymond et al., 2009 ). We concluded that a human head FE model was developed with capabilities to predict blunt- and ballistic-impact-induced skull fractures and pressure-related brain injuries.